Correlation of humeral length and its segments in a sample of Indian population: an osteological study - Samoon, Saima; Itoo, Mohd Saleem; Jan, Neelufur; Bhat, Gh. Mohd (International Journal of Research in Medical Sciences, 2018)
Background: Anthropometry measurements are very useful and have definite medico legal significance. In case of missing persons in the absence of pelvis and cranium, the remains of long bones of an individual play an important role in anthropological practice for morphometric analysis. The stature of an individual can be estimated from the humerus alone. Estimating the mean values of different segments of humerus helps in forensic and anthropometric practice. Previous studies have confirmed that humerus is one of the strongest long bones of the human skeleton and its fragments can be recorded in a forensic case. The present study was done to assess the mean values of different segments of humerus and their correlation with its length. Methods: Seventy dry adult humerus bones (32 rights and 38 left) were collected randomly from the anatomy department. Broken bones and the bones in a poor condition were excluded from the study. The segments of the humerus were studied for morphometric analysis. Results: All of the measurements were obtained in millimetres (mm). The measurement of the maximum length of humerus (MHH) was done by using an otseometric board and the different segments of humerus were measured by a vernier calliper (precision=0.cm). Mean and SD were calculated. Conclusions: This study has helped us to observe the maximum length of humerus and the mean values of the different segments of humerus in a sample of Indian population. The study also suggests that there are some differences between various segments of humerus within different populations.